Salivary Glucose and Oral Mucosal Alterations in Type II Diabetic Mellitus Patients - Sameeulla Shaik; Raviraj Jayam; Vijaykumar Bokkasam; Suresh Dirasantchu; Suman S Venkata; Sai Praveen (Wolters Kluwer Medknow Publications, 2017)
Aim: The study was undertaken: 1) To assess salivary glucose (SaG) levels in diabetic and nondiabetic subjects and to determine if saliva could be used as a noninvasive tool to diagnose and monitor Type II diabetes mellitus. 2) Correlation of SaG levels with serum glucose (SeG) levels in nondiabetic and diabetic patients. 3) To correlate the oral manifestations of diabetes mellitus with serum and SaG levels. Material and Methods: Both fasting and postprandial serum and SaG levels were analyzed from 70 Type II diabetic and 70 nondiabetic subjects. The detailed examination of oral cavity in relation to periodontal and dental status and subjective oral complaints were recorded. The obtained values were subjected to statistical analysis. Results: The mean fasting salivary glucose (FSaG) was 5.469 + 2.347 mg/dL and 7.634 + 4.468 mg/dL in nondiabetic and diabetics, respectively (P = 0.000) and postprandial salivary glucose (PSaG) was 6.434 + 2.111 mg/dL and 8.736 + 4.962 mg/dL in nondiabetic and diabetics, respectively (P = 0.000). The positive correlation was found between SeG levels and SaG in diabetics (P = 0.000). Strong positive correlation was observed between SeG and SaG with oral manifestations in Type II diabetic patients (P < 0.05). Conclusion: Saliva can be a useful tool in regular monitoring of "already diagnosed Type II diabetics" (by their SeG levels) rather than diagnosing subjects with "unknown status of diabetes mellitus." Strong positive correlation exists between SeG level and SaG level with oral manifestations in Type II diabetic patients.